2003
DOI: 10.1097/00008571-200302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase and susceptibility to organophosphorus poisoning in farmers dipping sheep

Abstract: The farmers reporting chronic ill health due to organophosphate exposure have a higher proportion of the PON1-192R polymorphism associated with lower rates of diazoxon hydrolysis and lower rates of diazoxon hydrolysis than the controls and that their ill health may be explained by a lower ability to detoxify diazoxon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 16 publications
3
60
2
3
Order By: Relevance
“…Although the prevalence of these OP genotypes varies in different setting, those of the minor alleles were low when compared to previous studies. 2,18,19 The combination of genotypic groups might also have resulted in the combination of risk and non-risk alleles, which would dilute the exposure/outcome association and shift it to the null.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the prevalence of these OP genotypes varies in different setting, those of the minor alleles were low when compared to previous studies. 2,18,19 The combination of genotypic groups might also have resulted in the combination of risk and non-risk alleles, which would dilute the exposure/outcome association and shift it to the null.…”
Section: Discussionmentioning
confidence: 99%
“…22 Although very few epidemiological studies have been conducted to determine the effects of the polymorphism on OP toxicity, all the published studies have reported the importance of PON1 and its allelic variants on OP susceptibility. 2,3,23,24 Furthermore, these studies were conducted in various settings, used different study designs, and investigated diverse health outcomes. These investigations focused on individuals exposed to OPs through sheep dipping in the UK, 2 poisoning of persons through suicide attempts (either orally or through an injection) in Turkey, 25 OP sprayers from public health programmes in India and South African farm workers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that individuals with the PON-1 RR192 and PON-1 LL55 allele were more likely to report symptoms of chronic OP exposure and feel ill, as compared to similarly employed controls who believed themselves to be healthy. This finding is likely due to the fact that individuals expressing the PON-1 RR192 and PON-1 LL55 alloforms are less efficient at hydrolyzing diazoxon, the major metabolite of diazinon, an OP found in the sheep dip [12].…”
Section: Op Compound Metabolism and Toxicitymentioning
confidence: 99%
“…In addition, slow metabolizers who also expressed PON-1 LL55 , which is associated with decreased PON-1 activity, were found to be the most likely persons to report symptoms of OP toxicity. [12] In addition, PON-1 fast metabolizers have been shown to have higher plasma and RBC cholinesterase levels than their counterparts who are slow metabolizers. [14] Together, these studies suggest a protective effect against OP toxicity in individuals who are PON-1 rapid metabolizers and have higher PON-1 activity.…”
Section: Op Compound Metabolism and Toxicitymentioning
confidence: 99%